Development of E-Flipbook Material on Changes in Electrical Energy, Motion Energy, Light Energy, and Heat Energy in Science Learning - Dwi Pika Wulandari; Aldina Eka Andriani (JURNAL PENDIDIKAN MIPA, 2026)
The limited use of interesting and interactive technology-based teaching materials causes student learning outcomes to be low. The purpose of this study is to describe the design of development, testing the feasibility, and effectiveness of the E-Flipbook for energy change materials to improve the learning outcomes of grade IV students of SDN Kalibanteng Kidul 03. This type of research R&D using the ADDIE model includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of 23 students in grade IV. Data collection techniques use non-tests (observations, interviews, questionnaires, and documentation) and tests (pretest and posttest). The data analysis technique used normality tests, t-test and N-Gain. The results show that the E-Flipbook is designed using the Canva and Heyzine applications equipped with learning videos, simple experiments, and interactive quizzes. The feasibility of the E-Flipbook was shown by the validation results of material experts of 92.86% and media experts of 92.11% of the category was very feasible and supported by the results of 97.5% of the teacher's response and 88.53% of the students' response in the very feasible category. The effectiveness of E-Flipbook was shown by an increase in learning outcomes by 15,296. The significance value was <0.001 and the N-Gain test result was 0.5714 in the medium category. In conclusion, the E-Flipbook has been successfully developed, very feasible and effective to be used to improve the learning outcomes of grade IV students of SDN Kalibanteng Kidul 03.